Evaluation of pollutants emissions into the atmospheric air of the Republic of Belarus using the results of processed forms of state statistic reporting 1 – air (Ministry of environment) - Hlazachova, Halina I.; Kurlovich, Tamara A.; Burak, Valery M.; Vagina, Tanya N. (Journal of the Belarusian State University. Ecology, 2018)
The quantitative and qualitative composition of air pollutant emissions from stationary sources of emissions in the Republic of Belarus was estimated on the basis of the annual state statistical observation data on form 1–air (Ministry of Environment). The analysis of emissions is presented in the territorial-administrative context (republic, region, Minsk, separate cities), as well as by types of economic activity. The dynamics of pollutant emissions into the atmosphere for the years of 2010–2016. The structure of emissions, the main pollutants for ingredients, the specific pollutants – by hazard class were analyzed. The issues of cleaning and neutralization of pollutants, as well as the use of pollutants caught by gas treatment plants are covered. Specific emissions (per 1 inhabitant and per sq. km of territory) are given. The estimation of pollutant emissions by economic activity. The analysis of summary statistical data on pollutants in the air will allow to interpret the available information and evidence-ensure that the necessary organizational and technological solutions to reduce the negative impact on the atmosphere.